A Classical Review on the Traditional Nutritional Food of India – Sattu - Singh, Preetpal; Vyas, Hitesh A; Patil, Sunny; Vasani, Dharmik; Vasava, Ashvinee (International Research Journal of Ayurveda & Yoga, 2023)
Objective: Sattu is one of the famous traditional foods of India. It is also used as medicine for treatment of many diseases, as dietary supplement for maintaining health and for prevention of different diseases. Aim of the present study was to compile and analyze the information regarding Sattu, available in various classical texts of Ayurveda. Data Sources: Ayurvedic texts mainly Brihattrayee comprising Charaka Samhita, Sushruta Samhita, Ashtanga Samgraha and Ashtanga Hridaya and various lexicons of Ayurveda were critically analyzed for the present review. Results: Sattu can be prepared from grains/cereals or medicinal plants or processed food articles. Sattu prepared from grains/cereals can be used as dietary supplement and Sattu prepared from medicinal plants can be used in various medical conditions or diseases as per the disease alleviating properties of the medicinal plant. Conclusion: Sattu is described by almost every classical text. In classics various properties of Sattu have been described in detail. Sattu is a nutritious food and its description is found in the form of Mantha as a regular drink for instant energy and strength.